(Nie)pełnosprawna starość – przyczyny, uwarunkowania, wsparcie - Gutowska, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
In this article we concentrated on the problem of disability in old age. This study presents: old age, aging process, disability and consequences disability in old age. Reflections on the support of older people with disability located and the end.